(untitled) (Research, Society and Development, 2024)
Technological advances can save lives and reverse the prognosis of many patients. One example is in relation to the benefits in the treatment of acute and chronic diseases in patients who depend on mechanical ventilation. We sought to verify what the scientific literature discusses about home ventilation assistance for children on mechanical ventilation. This study was characterized as an integrative literature review, with a qualitative approach, which was developed following six steps: identification of the topic and selection of the research question; establishment of criteria for inclusion and exclusion of studies (sampling); definition of information to be extracted from selected studies/categorization of studies; evaluation of included studies; interpretation of results; presentation of the review. Combinations of the health descriptors “home care”; “child” and “mechanical ventilation” - to search for articles in the Virtual Health Library. After research and application of the inclusion and exclusion criteria, seven articles were selected, which subsequently, following Bardin’s content analysis, were Organized into two categories, these highlighted the potential for ventilatory care at home for children and the main weaknesses in the process of care for children dependent on mechanical ventilation. Given the results of this bibliographical research, it was possible to verify that scientific technology is advancing considerably, as it is present in the hospital environment and depending on the disease, the residence is adapted to this entire technological apparatus, taking into account the benefits of this assistance, such as example, reduced exposure to hospital infections and greater family bonding.